CesA6 and PGIP2 Endocytosis Involves Different Subpopulations of TGN-Related Endosomes - De Caroli, Monica; Manno, Elisa; Perrotta, Carla; De Lorenzo, Giulia; Di Sansebastiano, Gian-Pietro; Piro, Gabriella (Frontiers in Plant Science, 2020)
Endocytosis is an essential process for the internalization of plasma membrane proteins, lipids and extracellular molecules into the cells. The mechanisms underlying endocytosis in plant cells involve several endosomal organelles whose origins and specific role needs still to be clarified. In this study we compare the internalization events of a GFP-tagged polygalacturonase-inhibiting protein of Phaseolus vulgaris (PGIP2-GFP) to that of a GFP-tagged subunit of cellulose synthase complex of Arabidopsis thaliana (secGFP-CesA6). Through the use of endocytic traffic chemical inhibitors (tyrphostin A23, salicylic acid, wortmannin, concanamycin A, Sortin 2, Endosidin 5 and BFA) it was evidenced that the two protein fusions were recycled through distinct endosomes with different mechanisms. PGIP2-GFP recycling is specifically sensitive to tyrphostin A23, salicylic acid and Sortin 2; furthermore, SYP51, a tSNARE with interfering effect on late steps of vacuolar traffic, affects its arrival in the central vacuole. SecGFP-CesA6, specifically sensitive to Endosidin 5, likely reaches the plasma membrane passing through the trans Golgi network (TGN), since the BFA treatment leads to the formation of BFA bodies, compatible with the aggregation of TGNs. BFA treatments determine the accumulation and tethering of the intracellular compartments labelled by both proteins, but PGIP2-GFP aggregated compartments overlap with those labelled by the endocytic dye marker FM4-64 while secGFP-CesA6 fills different compartments. Furthermore, secGFP-CesA6 co-localization with RFP-NIP1.1, marker of the direct ER-to-Vacuole traffic, in small compartments separated from ER suggests that secGFP-CesA6 is sorted through TGNs in which the direct contribution from the ER plays an important role. All together the data indicate the existence of an heterogenous population of Golgi-independent TGNs.